2004
DOI: 10.1038/sj.bjp.0705817
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐1D adrenoceptors are involved in reserpine‐induced supersensitivity of rat tail artery

Abstract: 1 We examined reserpine-induced chemical denervation supersensitivity with special reference to alpha-1 adrenoceptor (AR) subtypes. 2 Chronic treatment with reserpine for 2 weeks depleted noradrenaline in the tail artery and spleen of rats. Noradrenaline in the thoracic aorta was negligible before and after reserpine treatment. 3 The treatment with reserpine produced supersensitivity in the contractile responses of the rat tail artery to phenylephrine, 5-HT and KCl, resulting in leftward shift of concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 36 publications
(48 reference statements)
4
25
0
Order By: Relevance
“…Chronic inhibition of the adrenergic system results in increased responses to exogenous adrenergic agonists (Taki et al, 2004). In the present study increased responses to noradrenaline and phenylephrine were not observed in Dbh À/À mice.…”
Section: Change In Mean Arterialmentioning
confidence: 45%
“…Chronic inhibition of the adrenergic system results in increased responses to exogenous adrenergic agonists (Taki et al, 2004). In the present study increased responses to noradrenaline and phenylephrine were not observed in Dbh À/À mice.…”
Section: Change In Mean Arterialmentioning
confidence: 45%
“…However, the present study shows that both ␣-1L and ␣-1A ARs coexist in the intact tissue of rabbit ear artery. Recently, we have found that [ 3 H]KMD-3213 bound to only ␣-1A ARs in the intact segments of rat tail artery (I. Muramatsu, T. Tanaka, F. Suzuki, H. Yamamoto, Y. Hiraizumi-Hiraoka, and S. Morishima, unpublished data), where functional ␣-1A and ␣-1B ARs but not ␣-1L ARs have been demonstrated (Lachnit et al, 1997;Murata et al, 1999;Taki et al, 2004). Therefore, even though ␣-1A and ␣-1L ARs may be derived from the ␣-1L Adrenoceptor in Rabbit Ear Artery same gene, it is likely that both the subtypes are not necessarily expressed in parallel manner.…”
Section: Discussionmentioning
confidence: 99%
“…17,18) The results show hypertensive and vasoconstrictor effects of the radish leaves crude extract on the blood pressure of rats and vascular tissues from rabbit, possibly mediated through activation of α-adrenergic receptors. The effect on blood pressure observed in rodents appears to be mediated at relatively large doses, however, in view of the fact that small animals like rats and mice are known to have a more rapid metabolism (around 10 times faster) than humans, 19) the dose in humans for the hypertensive effect might have been close to 30 mg/kg.…”
Section: Resultsmentioning
confidence: 96%